2022
DOI: 10.21608/jppp.2022.159202.1092
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Fall Armyworm, Spodoptera frugiperda as A New Invasive Insect Pest on Maize Plants in the Nile Delta, Egypt

Abstract: Spodoptera frugiperda (Lepidoptera: Noctudiae) is an insect pest that attacks many crops around the world and causing large reductions in the crop yield, including Graminaceous crops, especially maize. This pest introduced Egypt from Sudan, was recorded for the first time in Egypt in 2019 at Aswan Governorate on corn plants, and recently recorded in Assiut Governorate in 2021. In this study, the presence of S. frugiperda was detected in the Nile Delta of the northern part of Egypt, since it was transferred fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Male forewings were brown and grey scaled with a white triangular patch at the apical and a circular spot in the mid of the wing. Both males and females have silvery white hind wings with a narrow dark margin (Rashed et al, 2022;Sharanbasappa et al, 2018b). The findings on damage and morphological characterization validate the species as S. frugiperda and this is the first confirmed report of this invasive species fall armyworm, Spodoptera frugiperda (J.E.…”
Section: Resultsmentioning
confidence: 99%
“…Male forewings were brown and grey scaled with a white triangular patch at the apical and a circular spot in the mid of the wing. Both males and females have silvery white hind wings with a narrow dark margin (Rashed et al, 2022;Sharanbasappa et al, 2018b). The findings on damage and morphological characterization validate the species as S. frugiperda and this is the first confirmed report of this invasive species fall armyworm, Spodoptera frugiperda (J.E.…”
Section: Resultsmentioning
confidence: 99%
“…It first appeared in Africa in January 2016 in Nigeria (Goergen et al, 2016). It was recorded in sub-Saharan Africa, (Abrahams et al, 2017) and in 2017, was also reported for the first time In Senegal by (Brévault et al, 2018) then by the Agricultural Pesticide Committee (APC) of the Ministry of Agriculture in Egypt where the first case was found in a maize field in a village in Kom Ombo city (Aswan Governorate, Upper Egypt) in 2019 then the northern part of Egypt (Rashed et al, 2022). This pest threatens the food security of more than 300 million people in Africa and may cause significant economic losses (FAO, 2018), as its large destructive impact could push 300 million people into hunger in Africa.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, by sowing maize during the fall season, as humidity increased, more insects and diseases arose, particularly fall armyworm insect. Where maize is the preferred host for fall armyworm insect in the countries (Rashed et al 2022). It can decrease annual maize yield from 21% to 53% without control methods (Huang et al 2020).…”
Section: The Effect Of Chitosan and Potassium Silicatementioning
confidence: 99%